Marriage Harmony: The Role Of Empathy And Forgiveness - Faisal Adnan Reza; Subhan Ajrin Sudirman; Mubarak Mubarak (Jurnal Studia Insania, 2021)
The phenomenon of forgiveness is an interesting behavior to discuss, especially in marital relationships. This article aims to examine the factors that influence forgiveness behavior in a marital relationship as well as to find out whether empathy is related to forgiveness behavior. The method used in this study is a mixed method with a population of 30 families or 60 subjects. The instruments used in addition to interviews were the scale of empathy and the scale of forgiveness. The analysis technique used is the Pearson correlation. The results showed that there was a significant relationship between empathy and forgiveness behavior. Meanwhile, the factors that influence forgiveness behavior are empathy, social and religious norms, interdependence between partners, and commitment.